PEMBELAJARAN INTEGRASI MELALUI MATERI TEMBANG DOLANAN DALAM MATA PELAJARAN BAHASA JAWA DI MI PLUS AL-KAUTSAR YOGYAKARTA - Nurul Ana Sulaikha (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2019)
This study aims to find out that religious values can be integrated through Javanese language learning in dolanan song material. This type of research is qualitative research with a field research approach (field research). The results showed that integration learning through dolanan song material in Javanese language subjects can instill religious values in students. In Javanese language learning must master all four language skills, namely: listening, reading, speaking, and writing. The results of the study show that from the four language skills can be integrated with religious values.